2019
DOI: 10.5114/pjr.2019.84602
|View full text |Cite
|
Sign up to set email alerts
|

Are type I dural arteriovenous fistulas safe? Single-centre experience of endovascular treatment of dural arteriovenous fistulas

Abstract: Introduction There are mixed reports on the incidence of intracranial haemorrhage in patients with dural arteriovenous fistulas. We assessed new proposed risk factors (i.a. number of outflows and outflow diameter) of intracerebral haemorrhage due to intracranial dural arteriovenous fistula and presented our personal experience in endovascular treatment of dural arteriovenous fistulas. Material and methods The patient database from January 2006 and December 2016 was revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The presence of large or giant venous aneurysm may prone to develop venous thrombosis after the decreasing the shunt flow. In a recent study, Brzozowski K et al 9 reviewed angiographic features of 25 DAVF patients and speculated mean outflow vein diameter might be associated with risk of hemorrhage before endovascular treatment. However, statistical analysis failed to recognize the association confined to the limited sample size.…”
Section: Conducted a Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of large or giant venous aneurysm may prone to develop venous thrombosis after the decreasing the shunt flow. In a recent study, Brzozowski K et al 9 reviewed angiographic features of 25 DAVF patients and speculated mean outflow vein diameter might be associated with risk of hemorrhage before endovascular treatment. However, statistical analysis failed to recognize the association confined to the limited sample size.…”
Section: Conducted a Systematic Reviewmentioning
confidence: 99%
“…Endovascular Onyx embolization has now been accepted as the primary treatment strategy to manage DAVFs. [5][6][7][8][9][10] There is still a lack of detailed information concerning the incidence and risk factors of hemorrhagic complications related to endovascular procedures. [2][3][4]6 In this article, we analyzed the possible risk factors for the hemorrhagic complication caused by endovascular embolization of DAVFs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 , 10 , 14 ] In general, fistulas occur in the areas of the transverse and sigmoid sinuses and can remain asymptomatic until the patient reaches middle age or older. [ 2 , 14 ] However, patients may report symptoms of serious neurological disorders often resulting from bleeding, so this condition requires appropriate therapeutic intervention. Treatment options typically include arterial and/or venous embolization followed by surgery or radiosurgery, as needed.…”
Section: Introductionmentioning
confidence: 99%
“…I read the article by Brzozowski et al about the percentage of intracranial haemorrhage in type I dural arteriovenous fistula with great interest [1]. In the paper, the authors demonstrated that 50% of patients with dural arteriovenous fistula presented with intracranial haemorrhage.…”
mentioning
confidence: 99%